LEGAL VACUUM IN INTERFAITH MARRIAGE RULES IN INDONESIA - Sidiqah, Meliyani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
The legal vacuum regarding the rules of interfaith marriage was not something new. However, this matter has not been resolved by the Government of Indonesia. After the Marriage Law’s promulgation, the rules of interfaith marriages